Numerical Analysis of the Crack Growth Path in the Cement of Hip Spacers (Fracture and Structural Integrity, 2022)
The use of temporary hip prosthesis made of orthopedic cement (spacer) in conjunction with antibiotics became a prevalent method used for prosthetic infections remedy; consequently, this method makes bone cement (PMMA) more fragile. Hence, the necessity of reinforcement incorporation is crucial to strengthen the bone cement. In this study, the finite element (FE) method was used to analyze the spacers behavior. FE model using an implicit integration method was used to simulate the mechanical behavior of the spacer under static loading. In addition, the extended finite element method (XFEM) was also used to investigate the fracture behavior of the non-reinforced and reinforced spacers. The results of this numerical analysis showed that the simulated crack initiation and propagation were in a good accordance with in vivo radiography and in vitro experimental observations. The full-stem reinforcement of 8 mm using reduce significantly the stress intensity factor and, consequently prevent the spacer fracture effectively. The FE models developed in this study contribute to help mechanical designers and engineers for prostheses’ quality and durability improvement.Abstract must be 200 words maximum, without figures or refs.
Keywords: Biomechanics; Hip Spacer; Bone Cement; Fracture; XFEM